Contribution of Gas Chromatography—Mass Spectrometry (GC-MS) to the Volatile Organic Compound Profile of Vespa velutina nigrithorax Larvae - Omaira de la Hera; Rosa María Alonso (Chemosensors)
Vespa velutina is an invasive species introduced by accident into Europe. Since its entry, it has spread rapidly and become a threat to biodiversity and beekeeping. Chemical communication between hornets is one of the main reasons for the proper functioning of hornet colonies. These signals can be from endogenous and/or exogenous chemical compounds. In this work, the volatile organic compound profile of Vespa velutina larvae was obtained by GC-MS previous solvent extraction procedures. A total of 99 volatile compounds were identified in the larvae volatile profile, of which 33 were common to adult hornets, suggesting a possible endogenous origin and a functional role in physiological processes and chemical communication within the colony. A total of 42 compounds were detected exclusively in the larvae, belonging to aldehydes, alcohols, alkanes, alkenes, amines, ketones, piperidines, pyrrolidines, furanones, fatty acid esters, ethers, and pyridines chemical families. The detection of these compounds in larval stages, before environmental exposure, supports the hypothesis of their endogenous origin. The findings of this work can contribute to widening the knowledge of the biology and chemical composition of V. velutina and could help identify potential semiochemicals useful for the design of more selective and sustainable strategies for its control.